An analysis of a framework of internal influential factors affecting the progress and outcomes of accreditation processes at the University of Curaçao - Sharine Isabella (Revista Educación Superior y Sociedad (ESS), 2019)
As of the beginning of this century, the University of Curaçao (UoC) started to implement preliminary activities to attain the accredited status for its programs by the Netherlands-Flemish Accreditation Organisation (NVAO). These exercises were highly successful since in its first attempt the UoC obtained the accredited status for the great majority of its programs. Based on a case study approach, in this paper the result of an analysis of these accreditation processes are presented to illustrate how the UoC has managed the great challenges encountered and to identify the internal factors that had an impact on the progress and outcomes of these processes. This study, which was as part of a PhD process, led to the design of a heuristic framework comprising of enablers and barriers affecting accreditation processes. This framework can generically be used as a descriptive, prescriptive and analytical instrument for the design, implementation and monitoring of accreditation processes, particularly in small universities.